Data visualization in Stata. (Packt Publishing, 2022)
It takes years of experience to accumulate knowledge of the different graphs and plots. This knowledge and visualizing experiences are packed in modular form; be a part of it. About This Video Learn basic methods of data visualization, variations, and customizations of visualization methods Gain experience of different data visualization techniques and how to apply them Implement code files along with bite-sized videos in a modular and easy-to-use approach In Detail Visualizing and graphing data is vital in modern data analytics. Whether you are a data scientist, student of quantitative methods, or a business user, having an understanding of how to visualize data is an important aspect of getting data information across to other stakeholders. Many ways of visualizing data have been devised and some are better than others. However, each method has advantages and disadvantages, and having a solid understanding of what visualization might be best suited is key to delivering a concise and sharp "data message". In this course, you will learn some of the most important data visualization methods. The author will also explain, without any equations or complex statistics, what are the advantages and disadvantages of each technique. You will be shown how each graph can be created, modified, and customized in Stata throughout the course's journey. This course will help you learn and understand the basic methods of data visualization. You will also learn, in an easy manner, variations and customizations of basic visualization methods. You will gain experience with different data visualization techniques and how to apply them. After understanding the techniques, you will learn and code many Stata graphs. Finally, you will gain confidence in your ability to modify and create bespoke data visualizations in Stata. By the end of this course, you will learn many different methods to visualize data and how to generate these yourself in Stata. Audience This course is ideally for Stata users, data analysts, data scientists, quantitative degree students, and quantitative business users that have a flair to explore this arena. Economists, social scientists, political scientists, biostatisticians, and other disciplines will also benefit from this course. Basic Stata knowledge along with some basic Stata coding (.do files, commands, varlists, and options) is an essential requirement to extract the most out of this course.